Estudo da secagem de sementes de mamão papaya (Carica papaya) em secador convectivo horizontal e leito de jorro e a influência na extração de óleo - Chielle, Daniel Padoin (2014)
During the papaya processing, 50% of the fruit is discarded as peel and seeds. The fruit central cavity contains 15% of fruit weight in seeds, which are potential products sources of high added value. The seeds, generally discarded, have high moisture content and high amount of oil, thus favoring the production of edible or essential oil or even biofuels. Based on this hypothesis, the aims of this study was to study the drying papaya seeds process in a horizontal convective dryer and spouted bed dryer, verify the controlled variables influence in each equipment on moisture reduction, oil yield and the influence over the fatty acid profile. The controlled variables were: temperature (T), speed (U) (min. 40 °C, 1 m s-1 and máx. 100 °C, 3 m s-1) to the convective dryer, and for the spouted bed dryer was temperature, speed and drying time (t) (min. 40 °C, 1,1Umj m s-1e 0,5 hours; max. 100 °C, 1,4Umj m s-1 e 4 ours), using Central Compound Rotational Design (CCRD). The result showed that for horizontal convective dryer, the lowest moisture (6% b.u.) was obtained with com T=91 °C e U=1,29 m s-1 and the oil yield (19,23%) with T=70 °C e U=2 m s-1. To the spouted bed dryer the lowest moisture (2,4% b.u.) with T=87,9 °C, U=1,34Umj m s-1 e t=3,29 hours and oil yield (26,50%) with com T=70 °C, U=1,25Umj e t=4 hours. There was not significant change on fatty acid compound between the experiments in both dryers.